Electrocatalytic Allylic C−H Alkylation Enabled by a Dual‐Function Cobalt Catalyst - Chen, Ming; Wu, Zheng‐Jian; Song, Jinshuai; Xu, Hai‐Chao (Angewandte Chemie International Edition, 2022)
The direct functionalization of allylic C−H bonds with nucleophiles minimizes pre‐functionalization and converts inexpensive, abundantly available materials to value‐added alkenyl‐substituted products but remains challenging. Here we report an electrocatalytic allylic C−H alkylation reaction with carbon nucleophiles employing an easily available cobalt–salen complex as the molecular catalyst. These C(sp3)−H/C(sp3)−H cross‐coupling reactions proceed through H2 evolution and require no external chemical oxidants. Importantly, the mild conditions and unique electrocatalytic radical process ensure excellent functional group tolerance and substrate compatibility with both linear and branched terminal alkenes. The synthetic utility of the electrochemical method is highlighted by its scalability (up to 200 mmol scale) under low loading of electrolyte (down to 0.05 equiv) and its successful application in the late‐stage functionalization of complex structures. An electrocatalytic allylic C−H alkylation reaction with carbon nucleophiles is reported, which employs an easily available cobalt–salen complex as the molecular catalyst. The method is characterized by its excellent functional group tolerance, substrate compatibility with both linear and branched terminal alkenes, and scalability (up to 200 mmol scale) with a low loading of electrolyte (down to 0.05 equiv).